Pengembangan Tanaman Kenaf (Hibiscus cannabinus L) pada Lahan Pasca Tambang Batubara - Roby Roby; Silvi Dwi Mentari (Soilrens, 2018)
Post coal mining activities in the village of Tanah Datar Muara Badak District, East Kalimantan Province, left vast vacant land. One of efforts to utilize the post-mining land through experimentation with kenaf (Hibiscus cannabinus L.) plant. Kenaf is a stem-fiber producer from the Malvaceae family, and currently receiving industrial attention. Kenaf plant can be utilized entirely, as industrial raw material with high commercial value. Kenaf also environmental-friendly and can absorb carbon dioxide from the atmosphere, therefore it is suitable to be developed as environmental-friendly industrial raw material. Kenaf species can grow in land with low nutrient status and toxic chemicals. The results show that kenaf plant can grow well on post coal mine land that has been treated previously with biochar and fertilizer. Biochar 100 Kg per plot in dosage combining with Mucuna sp.that spacing 30 x 30 cm give the best result for Kenaf growth both in diameter and plant height.  Keywords: land use, coal mine, kenaf, mucuna